Research on Development of Corn Production Decision Support System - Nan Lin; Dongming Li; Chunguang Bi (Indonesian Journal of Electrical Engineering and Computer Science, 2013)
This research was about the application of decision support system in agriculture. The subject of study was the corn cultivated in Jilin province, northeast of China. The research synthesized expertise and experience on corn cultivation, plant protection, soil and fertilizer, and synthesized agriculture ecology from experts, integrating computer technology, principle of decision support system with corn production knowledge. The research also concerned decision support system for corn fertilization and diagnosis of insect disease and weed harming, which included system concept design, database design, knowledge base design , model base design and preliminary inference engine design according to the characteristics of corn diseases and pests of weeds. DOI: http://dx.doi.org/10.11591/telkomnika.v11i7.2829